Anterior segment optical coherence tomography. (September 2018) - Ang, Marcus; Baskaran, Mani; Werkmeister, René M.; Chua, Jacqueline; Schmidl, Doreen; Aranha dos Santos, Valentin; Garhöfer, Gerhard; Mehta, Jodhbir S.; Schmetterer, Leopold
Abstract: Optical coherence tomography (OCT) provides non-contact, rapid in vivo imaging of ocular structures, and has become a key part of evaluating the anterior segment of the eye. Over the years, improvements to technology have increased the speed of capture and resolution of images, leading to the increasing impact of anterior segment OCT imaging on clinical practice. In this review, we summarize the historical development of anterior segment OCT, and provide an update on the research and clinical applications of imaging the ocular surface, cornea, anterior chamber structures, aqueous outflow system, and most recently anterior segment vessels. We also describe advancements in anterior segment OCT technology that have improved understanding with greater detail, such as tear film in dry eye disease evaluation, intra-operative real-time imaging for anterior segment surgery, and aqueous outflow with angle assessment for glaucoma. Improvements to image processing and software have also improved the ease and utility of interpreting anterior segment OCT images in everyday clinical practice. Future developments include refinement of assessing vascular networks for the anterior segment, in vivo ultra-high resolution anterior segment optical coherence tomography with histology-like detail, en-face image with 3-dimensional reconstruction as well as functional extensions of the technique. Highlights: Optical coherence tomography (OCT) technology has increased clinical applications in cornea and anterior segment imaging. Ultra-high resolution anterior segment OCT may provide in vivo 'histology' images of the cornea with greater detail. OCT enables better understanding of glaucoma mechanisms via imaging of the aqueous outflow system and angles. OCT of the tear film and corneal layers has improved understanding and treatment of dry eye disease. Non-invasive angiography of the anterior segment is now possible with novel OCT algorithms.